Manufacture of Cellular Glass Using Oak Leaves as a Foaming Vegetable Agent - Lucian Paunescu; Sorin Mircea Axinte; Marius Florin Dragoescu; Felicia Cosmulescu (Journal La Multiapp, 2020)
Abstract The manufacture experimentation of a cellular glass exclusively from mineral waste and natural residues using the unconventional technique of microwave irradiation was the objective of the research whose results are presented in the paper. The originality of the paper results from the use of oak leaves as a vegetable foaming agent as well as the use of microwave energy in heating processes of the raw material powder mixture for manufacturing thermal insulating materials for the building construction. Worldwide, these processes use only conventional heating techniques. The experimental results led to the conclusion that both the use of waste and residues, as well as the unconventional heating technique allow to obtain porous materials with structural homogeneity having apparent densities and thermal conductivities that can decrease up to 0.34 g/cm3, and 0.071 W/m·K respectively. The compressive strength corresponding to the materials with the lowest values of density and thermal conductivity has an acceptable value (1.2 MPa) for the field of application. The specific energy consumption is around 1 kWh/kg, being approximately at the same level with the values of industrial consumptions achieved by conventional techniques.